2016
DOI: 10.1111/vru.12334
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Appearance of the Temporomandibular Joint in 1018 Asymptomatic Horses: A Multi‐institution Study

Abstract: Published descriptions of nonseptic arthritis of the equine temporomandibular joint (TMJ) are rare and large studies investigating variations in the TMJ for asymptomatic horses are lacking. The objectives of this cross-sectional, retrospective, multi-institutional study were to describe anatomical variations in the TMJ detected using computed tomography (CT) in an equid population asymptomatic for TMJ disease and determine whether these variations were associated with patient signalment, reason for CT examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 21 publications
2
56
1
Order By: Relevance
“…A recent study analyzing more than 1000 equine TMJ by computed tomography has demonstrated a region of discrete linear mineralization in the articular disc (Carmalt et al, 2016), which closely resembles the lateral attractive singular point determined in the present study. Carmalt et al (2016) demonstrated that the appearance of this hyperdense zone is related to increasing age. It is likely that this age-dependent occurrence reflects the accumulation of ongoing mechanical stress, as previously demonstrated in the human TMJ (Jibiki et al, 1999).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A recent study analyzing more than 1000 equine TMJ by computed tomography has demonstrated a region of discrete linear mineralization in the articular disc (Carmalt et al, 2016), which closely resembles the lateral attractive singular point determined in the present study. Carmalt et al (2016) demonstrated that the appearance of this hyperdense zone is related to increasing age. It is likely that this age-dependent occurrence reflects the accumulation of ongoing mechanical stress, as previously demonstrated in the human TMJ (Jibiki et al, 1999).…”
Section: Discussionsupporting
confidence: 85%
“…Concomitantly, several studies have been performed to evaluate the suitability and potential relevance of advanced imaging techniques, i.e. radiography (Ebling et al, 2009), computed tomography (Rodríguez et al, 2008;Carmalt et al, 2016), ultrasonography (Rodríguez et al, 2007), magnetic resonance imaging (Rodríguez et al, 2010) and TMJ-arthroscopy (May et al, 2001;Weller et al, 2002). Besides these diagnostic and gross anatomical investigations, functional examinations of the equine masticatory movements have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, clinical diseases affecting the TMJ of horses appear relatively uncommon and in many instances the significance of TMJ lesions are hard to interpret. In a recent CT study of 1018 asymptomatic horses, anatomical variations were identified in the TMJs of 40 per cent of horses (Carmalt and others 2016). …”
Section: Iatrogenic Dysmastication Following Dental Treatmentmentioning
confidence: 99%
“…In this multi‐institution retrospective study James Carmalt and colleagues aimed to describe anatomical variations in the temporomandibular joint (TMJ) detected using computed tomography (CT) in an equid population asymptomatic for TMJ disease and determine whether these variations were associated with patient signalment, reason for CT examination, or CT slice width .…”
Section: Ct Imaging Of the Temporomandibular Jointmentioning
confidence: 99%